PENDUGAAN LAJU EROSI TANAH MENGGUNAKAN DATA SATELIT LANDSAT DAN SPOT - Trisakti, Bambang (Institut Teknologi Sepuluh Nopember, 2014)
The damage in catchment area (DTA) and the decrease of lake water quality have been happened in Indonesia, therefore Indonesian government has created a lake management and rescue program. This research aims to study soil erosion rate estimations using Landsat TM/ETM+ and SPOT-4 temporal data in the DTA of Kerinci Lake. Data standardization was carried out to maintain the consistency of the Normalized Difference Vegetation Index (NDVI) values from some disturbances caused by the differences of acquisition time, sensor and the effect of cloud cover. NDVImin and NDVImax were extracted from 19 Landsat TM / ETM + data in 2000-2009 period, slope was extracted from the Digital Elevation Model (DEM). Spatial distributions of soil erosion rate for 2009 and 2012 in the DTA were mapped using NDVI-slope method. The generated soil erosion rates in the DTA were analysed and verified by comparing the change of the soil erosion rate to the change of surface runoff coefficient. The results showed that the soil erosion rate in the DTA had a increasing trend, which is consistent with the increasing trend of surface runoff coefficient during 2009-2012 period. The soil erosion rate in the DTA of Lake Kerinci was estimated to increase form 0,39 mm/year in 2009 to be 0,46 mm/year in 2012.